Effect of Prolonged-Release Pirfenidone on Renal Function in Septic Acute Kidney Injury Patients: A Double-Blind Placebo-Controlled Clinical Trial - Jonathan S. Chávez-Iñiguez; Jorge L. Poo; Miguel Ibarra-Estrada; Leonel García-Benavides; Guillermo Navarro-Blackaller; Cynthia Cervantes-Sánchez; Eduardo Nungaray-Pacheco; Ramón Medina-González; Juan Armendariz-Borunda; Guillermo García-García (International Journal of Nephrology)
Background. There is no treatment for septic acute kidney injury (sAKI). The anti-inflammatory activity of prolonged-release pirfenidone (PR-PFD) could be beneficial in this clinical setting. Methods. This study was a double-blind randomized clinical trial in sAKI patients with nephrology consultation at the Civil Hospital of Guadalajara, in addition to the usual treatment of AKI associated with sepsis; patients were randomized to receive either PR-PFD at 1,200 mg/day (group A) or 600 mg/day (group B) or a matched placebo for 7 consecutive days. The primary objective was the decrease in serum creatinine (sCr) and increase in urinary volume (UV); the secondary objectives were changes in serum electrolytes, acid-base status, and mortality. Results. Between August 2016 and August 2017, 88 patients were randomized. The mean age was 54 (17 ± SD) years, and 47% were male. The main site of infection was the lung (39.8%), septic shock was present in 39.1% of the cases, and the mean SOFA score was 8.8 points. 28 patients received PFD 1,200 mg, 30 patients received PFD 600 mg, and 30 patients received placebo. During the study, sCr did not differ among the groups. The reversion rate of sCr, UV, and mortality was not different among the groups (p=0.70, p=0.47, and p=0.38, respectively). Mild adverse events were not different among the groups. Conclusion. PR-PFD did not improve the clinical course of sAKI and seemed to be safe in terms of adverse events. This trial is registered with NCT02530359.